2015
DOI: 10.1007/s12253-014-9872-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Villous Trophoblastic p38 and ERK1/2 Signaling Pathways in Preterm Preeclampsia and HELLP Syndrome

Abstract: Preterm preeclampsia is associated with the failure of trophoblast invasion, placental hypoxic/ischemic injury and the release of toxic substances, which promote the terminal pathway of preeclampsia. In term preeclampsia, factors yet unknown trigger the placenta to induce the terminal pathway. The contribution of the villous trophoblast to these pathologic events has not been fully elucidated. Here we aimed to study how stress and signaling pathways influence trophoblastic functions in various subforms of pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Additionally, if sVEGFR1 and soluble endoglin are given to pregnant rats, the animals not only develop preeclampsia but also liver dysfunction, thrombocytopenia, and intrauterine growth restriction(124); similar results have been obtained in mice(141). This condition is indistinguishable from the HELLP syndrome observed in humans(181184). …”
Section: Mechanisms By Which Metformin May Prevent Preeclampsiamentioning
confidence: 63%
“…Additionally, if sVEGFR1 and soluble endoglin are given to pregnant rats, the animals not only develop preeclampsia but also liver dysfunction, thrombocytopenia, and intrauterine growth restriction(124); similar results have been obtained in mice(141). This condition is indistinguishable from the HELLP syndrome observed in humans(181184). …”
Section: Mechanisms By Which Metformin May Prevent Preeclampsiamentioning
confidence: 63%
“…Preferential activation of p42/44 mapk and Akt is described in the foetoplacental vasculature from PE. Preterm PE (<37 wg) with HELLP (Hemolysis, Elevated Liver enzymes, and Low Platelet count) courses with increased phosphorylated p42/44 mapk activation in villous trophoblast [ 57 ]. In addition, the maternal plasma level from women with EOPE shows a higher level of endothelin-1 (ET-1) [ 58 ], but reduced Akt activity in the placenta [ 59 ] ( Figure 3 ).…”
Section: Insulin Resistance In Pregnancy Diseasesmentioning
confidence: 99%
“…Furthermore, a recent study also revealed that p38 phosphorylation was upregulated in PE placentas . Interestingly, a study reported that p38 phosphorylation was increased in preterm pre‐eclampsia, but remained unchanged in late onset pre‐eclampsia . It must be borne in mind that our data was generated using two distinct groups of control and PE women.…”
Section: Discussionmentioning
confidence: 79%